Intermolecular anharmonicity in molecular crystals: interplay between experimental low-frequency dynamics and quantum quasi-harmonic simulations of solid purine. Issue 26 (17th March 2017) - Ruggiero, Michael T.; Zeitler, J. Axel; Erba, Alessandro
Abstract : A combined experimental spectroscopic and theoretical quasi-harmonic investigation of intermolecular anharmonicity in crystalline purine. Abstract : The intermolecular anharmonic potential of crystalline purine is probed by means of temperature-dependent terahertz time-domain spectroscopy, low-frequency Raman scattering, X-ray diffraction, and ab initio quasi-harmonic quantum-chemical simulations. As temperature increases, anharmonicity in the intermolecular interactions results in strongly anisotropic thermal expansion – with a negative thermal expansion along the b crystallographic axis – yielding corresponding bulk structural modifications. The observed thermally-induced shifts of most vibrational bands in the terahertz region of the spectra are shown to arise from volume-dependent thermal changes of the hydrogen-bond pattern along the a and b crystallographic axes.